Assessment results analysis of vocational school leader's achievement motivation - Petrenko, L. M. (Visnyk of Vinnytsia Politechnical Institute, 2013)
Transformation trends in vocational education predetermine activation of human potentialities that drives the necessity of consideration of regularities of behaviour and related to it achievement motivation as a reliable predictor of efficient information and analytical activity and life-long personal development of vocational school leaders. The article examines the structure and content of components of achievement motivation, its assessment outcomes have been analyzed. The obtained data can be used in further research of this issue. They also indicate the advisability of specific recommendations for vocational school leaders on development of favourable environment for achievement motivation of vocational educational establishment managerial staff.